2019
DOI: 10.3390/su11030768
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Climate on Spatiotemporal Variations in Vegetation NDVI from 1982–2015 in Inner Mongolia, China

Abstract: By using the Global Inventory Modeling and Mapping Studies (GIMMS) third-generation normalized difference vegetation index (NDVI3g) data, this paper explores the spatiotemporal variations in vegetation and their relationship with temperature and precipitation between 1982 and 2015 in the Inner Mongolia region of China. Based on yearly scale data, the vegetation changes in Inner Mongolia have experienced three stages from 1982 to 2015: the vegetation activity kept a continuous improvement from 1982–1999, then d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 56 publications
(64 reference statements)
2
27
0
Order By: Relevance
“…Erodibility, as represented by threshold wind speed and DOR in spring, is related to the amount of precipitation or vegetation in the previous year, or both, according to observations in Mongolian grassland [33] and statistical analyses using synoptic data [7,13,14]. However, Liu et al [34] demonstrated that temperature has a greater impact on promoting vegetation growth than precipitation based on the one-year cycle; furthermore, temperature is the only determinative factor for a half-year changing in vegetation growth in Inner Mongolia. In accordance with their findings, our results suggested that temperature in autumn revealed a significant impact on erodibility.…”
Section: Discussionmentioning
confidence: 99%
“…Erodibility, as represented by threshold wind speed and DOR in spring, is related to the amount of precipitation or vegetation in the previous year, or both, according to observations in Mongolian grassland [33] and statistical analyses using synoptic data [7,13,14]. However, Liu et al [34] demonstrated that temperature has a greater impact on promoting vegetation growth than precipitation based on the one-year cycle; furthermore, temperature is the only determinative factor for a half-year changing in vegetation growth in Inner Mongolia. In accordance with their findings, our results suggested that temperature in autumn revealed a significant impact on erodibility.…”
Section: Discussionmentioning
confidence: 99%
“…where 2 S represents the variance of the observed values. In this study, the LISA map shows the spatial distribution (clustered/random/dispersed) of each vegetation index based on 9999 permutations at the significance level of p < 0.05.…”
Section: Spatial Autocorrelation Analysismentioning
confidence: 99%
“…As a major component of terrestrial ecosystems, vegetation plays an important role in material cycling and energy flows, and provides irreplaceable service functions that maintain the wellbeing of our planet and all the creatures that inhabit it. These function services include food provision, climate regulation, carbon sequestration, timber production, biodiversity preservation, and soil protection [1][2][3][4][5][6][7][8]. Vegetation growth affects the ecological balance, the terrestrial carbon cycle, water circulation, and other biochemical processes [2,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From East to West, the climate shows a zonal distribution. Accordingly, the grassland types of Inner Mongolia are divided into a meadow steppe to the west of the Daxinganling Mountains in eastern Inner Mongolia, a typical steppe in central Inner Mongolia, and a desert steppe in central and western Inner Mongolia [44,48] ( Figure 1). The climate of Inner Mongolia is dominated by continental monsoon climate.…”
Section: Study Areamentioning
confidence: 99%